Pengembangan Keterampilan Abad 21 Melalui Cara Berpikir Ilmiah, Etis, Dan Intuitif Di Satuan Pendidikan - Yudi Ruswandi; Asep Rijwan Suhendi (STAI Al-Mas'udiyah, 2023)
This research is motivated by the fact that in the current era of globalization, everyone is required to have special skills known as 21st-century skills. A qualitative approach is considered appropriate to be used to reveal the required data through the use of library research methods. The research results obtained are: 1) scientific thinking skills can be developed through learning with a scientific approach; 2) practicing ethical thinking is carried out with the habit of studying the Qur'an; 3) involving intuition in the learning process can train intuitive thinking; 4) in the context of mastering 21st-century skills, education units need to design interesting and meaningful learning according to learning objectives to develop scientific, ethical, and intuitive thinking skills. Following the results of the research, it can be concluded that efforts to improve 21st-century skills in education units are carried out by training, guiding, and directing students on scientific, ethical, and intuitive ways of thinking, through in-depth and meaningful learning experiences in each learning activity. Based on these conclusions, the education unit is to increase teacher competence, especially regarding pedagogic skills related to planning, implementing, evaluating, and following up on learning management that develops the ability to think scientifically, ethically, and intuitively students